The epidemic of erythromycin-resistant Bordetella pertussis with limited genome variation associated with pertussis resurgence in China. (1st November 2020) - Yao, Kaihu; Deng, Jikui; Ma, Xiang; Dai, Wenkui; Chen, Qiang; Zhou, Kai; Ye, Jinyan; Shi, Wei; Wang, Heping; Li, Dongfang; Wang, Hongmei; Wang, Jingmin; et al.
ABSTRACT: Background: The resurgence of Bordetella pertussis infections leading to whooping cough is a concern in many parts of the world. The number of pertussis cases in China has increased significantly since 2013. Research design and methods: In this study, whole-genome sequencing analysis was performed for 388 B. pertussis strains isolated in China from the 1970s to 2018, combining 594 published strains from around the world. Results: This study revealed that lineage V diverged about 50 years ago in China, while lineage IV is dominant in the other countries. It also revealed that the erythromycin-resistant sub-lineages Va, Vb, and Vc with limited genomic variation emerged 11 ~ 12 years ago. These three sub-lineages were identified after the co-purified acellular vaccines (cp-ACVs) completely replaced the previous whole cell vaccines (WCVs) after the national immunization program of 2012. It suggests that the cp-ACVs cannot induce immunity that is potent enough to restrict the spread of the lineage V, antibiotic abuse further favors the spread of this lineage in China. Conclusions: These findings demand a reassessment of the immunization strategy and development of new vaccines in China to stop the resurgence and drug resistance of B. pertussis .